MRI Characteristics of Ependymoblastoma: Results from 22 Centrally Reviewed Cases - Nowak, J.; Seidel, C.; Berg, F.; Pietsch, T.; Friedrich, C.; von Hoff, K.; Rutkowski, S.; Warmuth-Metz, M. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Ependymoblastoma is a malignant embryonal tumor that develops in early childhood and has a dismal prognosis. Categorized by the World Health Organization as a subgroup of CNS-primitive neuroectodermal tumor, ependymoblastoma is histologically defined by “ependymoblastic rosettes.” Because it is so rare, little is known about specific MR imaging characteristics of ependymoblastoma. We systematically analyzed and discussed MR imaging features of ependymoblastoma in a series of 22 consecutive patients. MATERIALS AND METHODS: Ependymoblastoma cases were obtained from the database of the German multicenter HIT trials between 2002 and 2013. All cases within this study were centrally reviewed for histopathology, MR imaging findings, and multimodal therapy. For systematic analysis of initial MR imaging scans at diagnosis, we applied standardized criteria for reference image evaluation of pediatric brain tumors. RESULTS: Ependymoblastomas are large tumors with well-defined tumor margins, iso- to hyperintense signal on T2WI, and diffusion restriction. Contrast enhancement is variable, with a tendency to mild or moderate enhancement. Subarachnoid spread is common in ependymoblastoma but can be absent initially. There was a male preponderance (1.75:1 ratio) for ependymoblastoma in our cohort. Mean age at diagnosis was 2.1 years. CONCLUSIONS: With this study, we add the largest case collection to the limited published database of MR imaging findings in ependymoblastoma, together with epidemiologic data. However, future studies are needed to systematically compare MR imaging findings of ependymoblastoma with other CNS-primitive neuroectodermal tumors and ependymoma, to delineate imaging criteria that might help distinguish these pediatric brain tumor entities. EBLependymoblastomaPNETprimitive neuroectodermal tumor